The effect of an induced hypercholesteremia on the regulation of the ARC gene expression, Brain Derived Neurotropic Factor (BDNF), Synapsing-1 and neurotransmitter –glutamate in male rats - Rafaish , Hadeel Ganai; Albazi , Wefak; Al-Aameli , Muna Hussain; Al-Thuwaini, Tahreer M.; Jhoni, Goosoon Hadi (Journal of Kerbala for Agricultural Sciences, 2024)
An abnormality of lipid metabolism known as hypercholesteremia, which causes blood cholesterol levels to be abnormally high, is a significant health concern. This research, in light of its association with neurodegenerative disease, is of paramount importance as it aims to elucidate how elevated cholesterol levels impact glutamate levels, BDNF, Synapsin K, and ARC gene expression. Ten male rats were meticulously assigned to a control group and another group that was given a 1% cholesterol supplement for 28 days. Each group received a random assignment of rats to ensure the validity of the results. Samples of homogenized brain tissue and serum blood were obtained after the experiment's completion, following a meticulous experimental design. Triacylglycerol (TAG), low-density lipoprotein (LDL), and total cholesterol (TC) values rose significantly, whereas HDL and brain-derived neurotrophic factor (BDNF) fell sharply, according to the study's findings. The results indicated that hypercholesteremia had a negative impact on glutamate levels, BDNF, and synapses due to oxidative stress, while synapsin-1 levels in brain tissue remained unchanged. There were also notable decreases in serum and homogenized brain tissue concentrations of NO and GSH, along with increases in MDA. Additionally, there was a noticeable decrease in glutamate levels in brain tissue and down-regulation of the Activity Cytoskeleton Association protein gene (ARC gene) expression.